External mission the ANC in exile, 1960-1990 - Ellis, Stephen 1953-2015 (2014)
Nelson Mandela's release from prison in February 1990 came a few days after the removal of the ban on the African National Congress (ANC); founded a century ago and outlawed in 1960, the ANC had transferred its headquarters abroad and opened what it termed an External Mission. For the 30 years following its banning, the ANC had fought relentlessly against the apartheid state. Finally voted into office in 1994, the ANC today regards its armed struggle as the central plank of its legitimacy. This book studies the ANC's period in exile, based on a full range of sources in southern Africa and Europe